Our favourite spots : intercultural learning in German as a foreign language through a video tandem project - Himmer, Johanna; Settari, Lisa (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2025)
This article presents a digital tandem project carried out by two OeAD lecturers as part of German as a foreign language courses. Bulgarian and Romanian students worked in small groups to create videos about their respective cities, which they then presented to their peers in the partner country. The project aimed to foster oral language skills in a creative and autonomous way, to experience and use German as an international language of communication, and to strengthen intercultural competences. In addition, each group analysed a partner video from the other city, which promoted deeper exchange, change of perspective, and the development of feedback skills. The article aims to provide insights into this practice-oriented teaching project and to encourage the implementation of similar intercultural learning formats in the field of teaching German as a foreign language.